Experimental investigation on microstructures and mechanical properties of PG4 flash-butt rail welds. (November 2022) - Pang, Yong; Grilli, Nicolò; Su, Hang; Liu, Wencheng; Ma, Jun; Yu, Siu Fung
Abstract: Flash-butt welding (FBW) has recently been employed to construct continuously welded rails. However, the failure mechanisms of FBW joints remain unclear. In this study, the weldability of mobile flash-butt welded joints was investigated in terms of microstructures, mechanical properties, and residual stresses. The microhardness test results indicated that the heat-affected zone (HAZ) of the PG4 welds showed significant reductions in hardness of up to 140 HV, whereas the digital image correlation (DIC) measurements showed high heterogeneous strains of up to 4%. Crystallographic analysis indicated that the grains in the HAZ underwent plastic strain with a lattice reorientation of approximately 80% and 55% in the face- and body-centred cubic phase, respectively. The uniaxial tensile tests established the phenomenological relationship between the bond strength and HAZ width: specifically, the bond strength was relatively high at the foot and head of the rail, progressively decreased at the web, and was inversely correlated with the HAZ width. A fractographic analysis confirmed that the shrinkage cracks, inclusions, and flat spots in the rail web were the main cause of early failure in uniaxial tensile tests. Residual stress measurements also showed that FBW can introduce high residual stresses in the rail web of up to 436.76 ± 18.10 MPa and 225.80 ± 12.94 MPa in the vertical and longitudinal directions, respectively. The results of this study reveal that the bond strength of mobile FBW can be assessed based on their HAZ width and provide reliable guidelines for improving the safety and stability of railway systems. Graphical abstract: Highlights: Flash-butt welding technology was applied to join pearlite rail steels. Microstructure, bond strength, and residual stress of flash-butt welds were studied. Grain misorientation in flash-butt rail welds was quantitively analyzed. Phenomenological relationship between bond strength and HAZ width was established.